2013
DOI: 10.1136/bcr-2013-010047
|View full text |Cite
|
Sign up to set email alerts
|

Cutis verticis gyrata as a clinical manifestation of Touraine-Solente-Gole’ syndrome (pachydermoperiostosis)

Abstract: SUMMARYCutis verticis gyrata is a descriptive term for a condition of the scalp consisting of deep grooves and convolutions that resemble the surface of the brain. We present a case of a 22-year-old man who presented with pain and swelling of both knees and hands. Enlarged wrists, ankles and feet were also noted, along with facial seborrhoea, thickening of the skin and deformity of the fingers. Physical examination of the scalp showed a cerebriform appearance with accentuating folds and deep furrows (cutis ver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 8 publications
(7 reference statements)
0
5
0
Order By: Relevance
“…8 PGE2 may mimic the activity of osteoblasts and osteoclasts, and may be responsible for acro-osteolysis and formation of periosteal bone, in addition, it has vasodilator effects that may be responsible for prolonged local vasodilation, resulting in digital clubbing. 4 The combination of skin thickening and bone enlargement may result in large enlargement of the extremities -enlargement similar to abutment of the lower limbs 1,11 striking physical findings of our patient. An aged appearance, often seen, was observed because of thickened, wavy skin.…”
Section: Discussionmentioning
confidence: 53%
“…8 PGE2 may mimic the activity of osteoblasts and osteoclasts, and may be responsible for acro-osteolysis and formation of periosteal bone, in addition, it has vasodilator effects that may be responsible for prolonged local vasodilation, resulting in digital clubbing. 4 The combination of skin thickening and bone enlargement may result in large enlargement of the extremities -enlargement similar to abutment of the lower limbs 1,11 striking physical findings of our patient. An aged appearance, often seen, was observed because of thickened, wavy skin.…”
Section: Discussionmentioning
confidence: 53%
“…Several genes, such as HPGD, prostaglandinendoperoxidase synthase (PTGS) 1, PTGS2, prostaglandin E synthase (PTGES), PTGER1, prostaglandin E receptor (PTGER) 2, PTGER3, PTGER4, SLCO2A1, SLCO3A1, SLCO4A1, and PTGR2, are involved in the biosynthesis and signaling pathway of PGE2 [7]. A recent analysis suggested that patients with prostaglandin transporter SLCO2A1 mutations are more likely to develop myelofibrosis [8].…”
Section: Discussionmentioning
confidence: 99%
“…The latter type can manifest in areas other than the scalp and has been associated with different conditions, such as acromegaly and pachydermo-periostosis. 6,7 Furthermore, CVG has been described among patients receiving external-beam whole-brain radiotherapy, vemurafenib and anabolic steroids. 8,9 Primary essential CVG may also be associated with certain genetic disorders, like fragile X syndrome.…”
Section: Commentmentioning
confidence: 99%